Care pathways models and clinical outcomes in Disorders of consciousness. Issue 8 (21st July 2017) - Sattin, Davide; Morganti, Laura; De Torres, Laura; Dolce, Giuliano; Arcuri, Francesco; Estraneo, Anna; Cardinale, Viviana; Piperno, Roberto; Zavatta, Elena; Formisano, Rita; D'Ippolito, Mariagrazia; Vassallo, Claudio; et al.
Abstract: Objective: Patients with Disorders of consciousness, are persons with extremely low functioning levels and represent a challenge for health care systems due to their high needs of facilitating environmental factors. Despite a common Italian health care pathway for these patients, no studies have analyzed information on how each region have implemented it in its welfare system correlating data with patients' clinical outcomes. Materials and Methods: A multicenter observational pilot study was realized. Clinicians collected data on the care pathways of patients with Disorder of consciousness by asking 90 patients' caregivers to complete an ad hoc questionnaire through a structured phone interview. Questionnaire consisted of three sections: sociodemographic data, description of the care pathway done by the patient, and caregiver evaluation of health services and information received. Results: Seventy‐three patients were analyzed. Length of hospital stay was different across the health care models and it was associated with improvement in clinical diagnosis. In long‐term care units, the diagnosis at admission and the number of caregivers available for each patient (median value = 3) showed an indirect relationship with worsening probability in clinical outcome. Caregivers reported that communication with professionals (42%) and the answer to the need of information were the most critical points in the acute phase, whereas presence of Non‐Governmental Organizations (25%) and availability of psychologists for caregivers (21%) were often missing during long‐term care. The 65% of caregivers reported they did not know the UN Convention on the Rights of Persons with Disabilities. Conclusion: This study highlights relevant differences in analyzed models, despite a recommended national pathway of care. Future public health considerations and actions are needed to guarantee equity and standardization of the care process in all European countries. Abstract : Length of hospital stay was different across the health care models and it was associated with probability of an improvement in clinical diagnosis. Caregivers reported that communication with professionals, the answer to the need of information, and the presence of NGOs were the most critical points in the health care for persons with Disorders of consciousness. Future public health considerations and actions are needed to guarantee equity and standardization of the care process in all European countries.